Rancang Bangun Alat Monitoring Suhu Dan Kelembaban Berbasis Internet Of Things (IOT) Pada Gudang Obat Rumah Sakit Aryoko Sorong: Rancang Bangun Alat Monitoring Suhu Dan Kelembaban Berbasis Internet Of Things (IOT) Pada Gudang Obat Rumah Sakit Aryoko Sorong - Pandu Diaz Nugraha; Rendra Soekarta; Irman Amri (Universitas Muhammadiyah Sorong, 2023)
Proper temperature control and monitoring in hospital drug storage plays an important role in maintaining the quality and safety of stored drugs. In this research, we propose an Internet of Things (IoT) based temperature monitoring system using NodeMCU ESP8266 with DHT22 sensor. The purpose of this research is to monitor the temperature of the pharmacy in real time and provide access to temperature data through mobile devices with the Blynk platform. Testing is done by designing and implementing hardware including ESP8266 NodeMCU as a microcontroller and DHT22 temperature sensor as a thermometer. The ESP8266 Node MCU was programmed to periodically collect temperature data from the DHT22 sensor and send it to the Thingspeak cloud platform for storage. The Thingspeak platform was chosen due to its ability to provide data storage and graphing services for visual data observation. Therefore, this research presents a practical solution for temperature monitoring in the pharmacy of Aryoko Korem Hospital. The use of ESP8266 NodeMCU with DHT22 sensor and the integration of Thingspeak and Blynk improve monitoring efficiency and maintain the quality of stored drugs in a critical pharmacy environment.